1+1/2^3+1/3^3+1/4^3+----
Answers
1³/1 + (1³ + 2³)/(1 + 3) + ( 1³ + 2³ + 3³)/(1 + 3 + 5)+.....
Tₙ = ( nth term of numerator )/( nth term of denominator )
= (1³ + 2³ + 3³ + ...... n terms )/(1 + 3 + 5 + .... n terms )
nth term of numerator = 1³ + 2³ + 3³ + ..... n terms
= ∑n³ = [n(n + 1)/2]²
nth term of denominator = 1 + 3 + 5 + ...... + n terms
= n/2 {2 × 1 + ( n - 1) × 2 }
= n²
Tₙ = n²( n + 1)²/4n² = ( n + 1)²/4
S = ∑Tₙ
=1/4 ∑(n + 1)²
= 1/4 (∑n² + 2∑n + ∑1 )
we know,
∑n² = n( n + 1)(2n + 1)/6
∑n = n(n + 1)/2
∑1= n
Sₙ = 1/4 { n(n + 1)(2n + 1)/6 +2n(n + 1)/2 + n }
= 1/4 {n(n + 1)(2n + 1)/6 + n(n + 1) + n}
= n/24 { 2n² + 9n + 13 }
hence,
sum of n terms = n/24 { 2n² + 9n + 13 }
Answer:
1³/1 + (1³ + 2³)/(1 + 3) + ( 1³ + 2³ + 3³)/(1 + 3 + 5)+.....
Tₙ = ( nth term of numerator )/( nth term of denominator )
= (1³ + 2³ + 3³ + ...... n terms )/(1 + 3 + 5 + .... n terms )
Step-by-step explanation: